Electroencephalographic theta oscillatory dynamics reveal attentional bias to angry faces. (24th August 2017) - Diao, Liuting; Qi, Senqing; Xu, Mengsi; Fan, Lingxia; Yang, Dong
Highlights: Angry faces elicited a shorter RT and enhanced N2pc compared to happy faces. Angry faces induced heightened theta oscillation as opposed to happy faces. Theta oscillation may represent the preferential processing of threatening faces. Abstract: Although previous studies have reported the temporal neural dynamics (e.g., N2pc component) of threat-detection orientation for face-processing (e.g., the "anger superiority effect"), little is known about the neural oscillatory features of this phenomenon. Here, we extracted the event-related potentials and event-related oscillatory power dynamics from electroencephalographic data when participants performed a visual search task consisting of realistic angry, happy, and neutral facial expressions. We observed a shorter response time and a larger N2pc for angry faces than for happy faces, suggesting the existence of preferential processing for angry faces. Similarly, elevated theta synchronization was observed for angry faces compared to happy faces, while both angry and happy faces elicited heightened theta oscillatory activity on contralateral location of target face compared to ipsilateral location. Moreover, the theta oscillation difference negatively correlated with the amplitude of the N2pc difference. Our findings suggest that the occipital theta oscillation is engaged in the search advantage of angry facial expressions. Further, our results provide evidence that the theta oscillation may reflect the processing dynamics of threat-stimuli orientation in an ever-changing environment.